Mechanism of Lending to the Agri-Industrial Complex in the EAEU Countries - TAIPOV, Timur Alchinovich; OMARBAKIEV, Lutpulla Amurullamovich; NIZAMDINOVA, Arzigul Kamirdinovna; ESAIDAR, Urzada Serimkyzy; ZHANGUTINA, Gulnar Olzhabayevna (Journal of Advanced Research in Law and Economics; Vol 7 No 1 (2016): JARLE Volume VII, Issue 1(15), Spring 2016, 2016)
The most important part of the agri-industrial complex is the agriculture, which provides the country with food products and industry with raw materials, and generates income in different sectors of economy, contributing to the development of agricultural production, the increase of its solvency and the level of material and technical basis. In the process of integration and intensification it is important to establish a common financial market, ensuring efficient allocation of capital, which allows to diversify risks and increase competition in the financial service market. By 2020 it is planned to complete the processes of the unification of national legislations in the field of financial services and the convergence of approaches to the regulation of activities in the financial sector and development of a unified strategy for financial market development. The article includes the analysis of the lending experience in the countries of the Eurasian Economic Union, the agricultural policy of the EAEU countries in the field of lending and the evaluation of its adaptability in Kazakhstan, shows the conditions for cost-effective integration and cooperation, types of loans in the agri-industrial sector of the country.